Eating concerns, body dissatisfaction, thinness internalization and antifat attitudes and their relationship with gender ideology in a sample of men - Magallares, Alejandro (Anales de Psicología / Annals of Psychology, 2015)
Eating disorders are much less common in men than in women. In this paper it is argued that these differences may be explained by the gender ideology that men and women have. Literature suggests that women’s ideology internalizes the social norm of slimness and for that reason may develop eating concerns and body dissatisfaction with the pass of the time, while men externalize the value of thinness and that is why they show greater antifat attitudes than women. Data obtained from 450 male students revealed that participants high in a gender ideology scale reported greater antifat attitudes and less thinness internalization, eating concerns and body dissatisfaction. Finally, it is discussed why men and women adopt different strategies to deal with the social norm of thinness.